Are the primary characteristics of polystyrene nanoplastics responsible for toxicity and ad/absorption in the marine diatom Phaeodactylum tricornutum?. (June 2019) - Sendra, Marta; Staffieri, Eleonora; Yeste, María Pilar; Moreno-Garrido, Ignacio; Gatica, José Manuel; Corsi, Ilaria; Blasco, Julián
Abstract: Nowadays, the occurrence of a large volume of plastic litter in oceanic and coastal zones has increased concern about its impacts on marine organisms. The degradation of plastic polymers leads to the formation of smaller fragments at both micro and nano scale (<5 mm and <1 μm respectively). Nanoplastics (NPs), due to their smaller size and high specific surface area can establish colloidal interactions with marine microalgae, therefore potential toxicity can be led. . To assess this hypothesis, the aim of the present study is to examine the behaviour of polystyrene nanoparticles (PS NPs) of different sizes (50 and 100 nm) in marine water and their possible effects at different physiological and cellular levels in the marine diatom Phaeodactylum tricornutum . Different biomarkers and stress responses in P. tricornutum were analysed when organisms were exposed to environmentally relevant PS NPs concentrations between 0.1 and 50 mg L −1 . Our results showed significant differences between controls and exposure microalgae, indicating toxicity. After 24 h, an increase in oxidative stress biomarkers, damage to the photosynthetic apparatus, DNA damage and depolarization of mitochondrial and cell membrane from 5 mg L −1 were observed. Further after 72 h the inhibition of population growth and chlorophyll content were observed. Examining effects the effects related to PS NPs size, the smallest (50 nm) induced greater effects at 24 h while bigger PS NPs (100 nm) at72 h. This bigger particles (100 nm) showed more stability (in size distribution and spherical form) in the different culture media assayed, when compared with the rest of particles used. Strong adsorption and/or internalization of PS NPs was confirmed through changes in cell complexity and cell size as well as the fluorescence of 100 nm fluoresbrite PS NPs after washing cell surface. Graphical abstract: Image 1 Highlights: Agglomeration of Polystyrene nanoplastics is unstable in seawater. P. tricornutum showed toxicity responses when it was exposed to Polystyrene nanoplastics. Microalgae was more affected by the biggest plastic particles (100 nm). Internalization or strong adsorption of plastics in/on algal cells was stated.